Performance optimization of dual stage algorithm for lossless data compression and decompression - Shirakol, Shrikanth; Koparde, Akshata; ., Sandhya; Kulkarni, Shravan; Kini, Yogesh (International Journal of Engineering and Technology, 2018)
In this paper, an optimized dual stage architecture is proposed which is the combination of Lempel-Ziv-Welch (LZW) Algorithm at the first phase and Arithmetic Coding being the later part of Architecture. LZW Algorithm is a lossless compression algorithm and code here for each character is available in the dictionary which reduces 5-bits per cycle as compared to ASCII. In arithmetic coding the numbers are represented by an interval of real numbers from zero to one according to their probabilities. It is an entropy coding and is lossless in nature. The text information is allowed to pass through the proposed architecture and it gets compressed to the higher rate.Â Â